Dynamics of transcription is affected by oxygen tension and developmental speed during in vitro production of bovine embryos - de Lima, Camila Bruna; do Amaral, Danilo Trabuco; Ispada, Jéssica; dos Santos, Érika Cristina; Fontes, Patrícia Kubo; Nogueira, Marcelo Fábio Gouveia [UNESP]; Milazzotto, Marcella Pecora (Wiley, 2024)
This study examines the impact of oxygen tension and embryo kinetics on gene transcription dynamics in pathways crucial for embryonic preimplantation development, including lipid metabolism, carbohydrate transport and metabolism, mitochondrial function, stress response, apoptosis and transcription regulation. Bovine embryos were generated in vitro and allocated into two groups based on oxygen tension (20% or 5%) at 18 h post insemination (hpi). At 40 hpi, embryos were categorized into Fast (≥4 cells) or Slow (2 cells) groups, resulting in four experimental groups: FCL20, FCL5, SCL20 and SCL5. Embryo collection also occurred at 72 hpi (16-cell stage; groups FMO20, FMO5, SMO20 and SMO5) and at 168 hpi (expanded blastocyst (BL) stage; groups FBL20, FBL5, SBL20 and SBL5). Pools of three embryos per group were analysed in four replicates using inventoried TaqMan assays specific for Bos taurus, targeting 93 genes. Gene expression patterns were analysed using the K-means algorithm, revealing three main clusters: genes with low relative abundance at the cleavage (CL) and 16-cell morula (MO) stages but increased at the BL stage (cluster 1); genes with higher abundances at CL but decreasing at MO and BL (cluster 2); and genes with low levels at CL, higher levels at MO and decreased levels at BL (cluster 3). Within each cluster, genes related to epigenetic mechanisms, cell differentiation events and glucose metabolism were particularly influenced by differences in developmental kinetics and oxygen tension. Fast-developing embryos, particularly those cultured under low oxygen tension, exhibited transcript dynamics more closely resembling that reported in vivo-produced embryos.
Keywords: bovine; development; embryo; oxygen tension